Development and validation of a questionnaire measuring knowledge, attitudes, and current practices of primary healthcare physicians regarding road injury prevention in older adults. (30th November 2021) - Jiménez-Mejías, Eladio; Rivera-Izquierdo, Mario; Miguel Martín-delosReyes, Luis; Martínez-Ruiz, Virginia; Molina-Soberanes, Daniel; Rosa Sánchez-Pérez, María; Lardelli-Claret, Pablo
Abstract: Background: Older adults present high risk of involvement in road crashes. Preventive interventions conducted by their primary healthcare physicians (PHPC) could reduce this public health issue. Objective: The objective of this study was to design and validate a self-administered questionnaire that measures the knowledge, attitudes, and current practices (CP) of PHCP in Spain regarding the prevention of road injuries in older adults. Methods: One thousand eight hundred and ninety-seven PHCP completed a questionnaire piloted previously in an expert panel and two convenience samples of physicians. It comprised 78 items grouped in five sections and was mainly focused on exploring three constructs: knowledge, attitudes, and CP. Exploratory factor analysis was used to obtain evidence of internal structure validity. Reliability was assessed through Cronbach's α coefficient. Correlation coefficients for the scores constructed for each of the extracted factors were calculated to assess convergent and discriminant validity. Results: Factor analysis extracted four factors each for the knowledge and attitudes constructs, and three factors for the CP construct, which explained more than 55% of the variance in each construct. Except for two factors of the knowledge construct regarding existing health problems associated to the risk of involvement in road crashes, the clustering pattern of all other items across the remaining nine factors was consistent and in agreement with previous knowledge. Cronbach's α values were greater than 0.7 for all constructs. Conclusions: Our questionnaire appears to be valid enough to assess the attitudes, CP, and medication-related knowledge of PHCP in Spain regarding the prevention of road injuries in older adults.